Laboratory mouse housing conditions can be improved using common environmental enrichment without compromising data - André, Viola; Gau, Christine; Scheideler, Angelika; Aguilar-Pimentel, Juan A.; Amarie, Oana V.; Becker, Lore; Garrett, Lillian; Hans, Wolfgang; Hölter, Sabine M.; Janik, Dirk; Moreth, Kristin; Neff, Frauke; et al. (PLOS Biology, 2018)
Author summary Adequate housing of laboratory animals is essential to guarantee their well-being. From a scientific perspective, physically and mentally healthy animals also contribute to increased validity and reproducibility of experimental results. The choice of nesting material or shelter type, referred to as environmental enrichment, may influence how laboratory animals perform species-specific behaviors. Consequently, changes in these nesting and shelter materials could influence scientific results by, for example, increasing variability in measured characteristics. Whether studies using different environmental enrichment materials can be compared is currently questioned. Our study shows that simple, species-specific environmental enrichment in the form of nesting material alone or in combination with a shelter did not consistently increase variability of physiological parameters in mice. Differences in parameter average values appeared to be of minor biological relevance when compared to the effects of other environmental factors. These simple environmental enrichment devices may therefore be applied to improve the housing environment of laboratory mice without compromising data validity or comparability.